Algunos conceptos sobre la necesidad de reposición de nutrientes en plantaciones forestales de la provincia de Misiones = Some concepts on the need for nutrient reposition in forest plantations in the Misiones province - Martiarena, Rodolfo; Von Wallis, Alejandra; Pahr, Norberto Manuel; Lupi, Ana Maria (Facultad de Ciencias Forestales, Universidad Nacional de Misiones, 2025)
The objective of the present work was to identify the importance of the fertilizing aggregate during the plantation establishment and its effect on the different forest species cultivation in the Misiones province. The applied methodology was similar for the installed assay wich results showed general trends that provide useful information for forest management in the region.